The true Tectaria chinensis (Tectariaceae): morphology, distribution, and allied species - Dong, Shi-Yong; Tan, Shi-Shi; Pham, van The; Phan, Ke Loc (Phytotaxa, 2018)
Tectaria chinensis is a poorly known species from China, with its type being the sole authentic voucher to date. Recent field observations and morphological comparisons reveal its type being an incomplete frond, which resulted in the constant misinterpretation of some morphological characters and the allied species to T. chinensis. In fact, T. chinensis is a very special species restricted in southern China and northern Vietnam and featured by the unique long and erect caudex and the rare combination of partly free venation and vein-dorsal sori. Phylogenetically, T. chinensis was revealed by our previous analyses of five plastid regions to be in the Ctenitopsis group (Clade III or T. subg. Ctenitopsis), forming a sister clade to the lineage of T. fuscipes. A detailed description, explanatory illustrations, as well as distribution and habitat information of T. chinensis are provided.